Criticism of Pure Legal Theory Thought Critical Legal Studies (Critical Legal Studies) and its Relevance to the Indonesian Legal System - Muhamad Ridwan Kafara (Budapest International Research and Critics University, 2022)
The pure theory of law (pure legal theory), which desires that the law must be free from non-legal elements such as politics, economics, society and others is an essential part of pure legal theory. Legal positivism is known for the importance of the separation between law and morals. In addition, even for positivists, cruel legal norms can be accepted as law on the condition that the formal criteria regarding the law are met. The view of pure legal theory, which assumes that law must be separated from other fields of science, has been criticized by Critical Law Studies (CLS), which assumes that law is always intervened by interests outside the law so that law is never neutral and objective. This means that law cannot be separated from politics because the law is not formed in a value-free vacuum. The thought of Critic Law Studies (CLS) lies in the fact that law is politics (law is politics). Hence, Critic Law Studies (CLS) rejects and attacks the beliefs of positivists in legal science. Critic Law Studies (CLS) criticizes the applicable law for being politically biased and never neutral.